Depletion of Gut Microbiota Protects against Renal Ischemia-Reperfusion Injury - Emal, Diba; Rampanelli, Elena; Stroo, Ingrid; Butter, Loes M; Teske, Gwendoline J; Claessen, Nike; Stokman, Geurt; Florquin, Sandrine; Leemans, Jaklien C; Dessing, Mark C (Journal of the American Society of Nephrology, 2017)
An accumulating body of evidence shows that gut microbiota fulfill an important role in health and disease by modulating local and systemic immunity. The importance of the microbiome in the development of kidney disease, however, is largely unknown. To study this concept, we depleted gut microbiota with broad-spectrum antibiotics and performed renal ischemia-reperfusion (I/R) injury in mice. Depletion of the microbiota significantly attenuated renal damage, dysfunction, and remote organ injury and maintained tubular integrity after renal I/R injury. Gut flora-depleted mice expressed lower levels of F4/80 and chemokine receptors CX3CR1 and CCR2 in the F4/80 renal resident macrophage population and bone marrow (BM) monocytes than did control mice. Additionally, compared with control BM monocytes, BM monocytes from gut flora-depleted mice had decreased migratory capacity toward CX3CL1 and CCL2 ligands. To study whether these effects were driven by depletion of the microbiota, we performed fecal transplants in antibiotic-treated mice and found that transplant of fecal material from an untreated mouse abolished the protective effect of microbiota depletion upon renal I/R injury. In conclusion, we show that depletion of gut microbiota profoundly protects against renal I/R injury by reducing maturation status of F4/80 renal resident macrophages and BM monocytes. Therefore, dampening the inflammatory response by targeting microbiota-derived mediators might be a promising therapy against I/R injury.